Crisis in teaching the qualitative methodology (Andamios, Revista de Investigación Social, 2016)
The new methodological debates within social sciences aim at overcoming the antagonism between the quantitative and the qualitative characteristics and propose the mixed, or triangulation comprehensive approach; however, these proposals present mistakes in two specific directions: 1. There is still a lack of understanding of the epistemological origin of each one of these approaches, which involves giving a secondary range to qualitative characteristics when trying to integrate both methodologies, and 2. Considering the data collection techniques are inherently qualitative methods. It is considered that some of these mistakes are related to poor education that is made of qualitative methodology at postgraduate level.
Keywords: Qualitative methodology; quantitative methodology; collection techniques mixed approach; epistemology; qualitative methodology teaching